Emotional Intelligence of Agricultural Officers of Kerala State Department of Agriculture - Victor, Reshma A; A, Anilkumar (Journal of Extension Education, 2020)
The present study was conducted in the three zones of Kerala viz., Kasaragod from North Kerala, Thrissur from Central Kerala and Thiruvananthapuram from South Kerala. In this study an attempt has been made to measure the emotional intelligence of panchayat level Agricultural Officers of Kerala State Department of Agriculture, under Krishi Bhavan System. A sample of 90 Agricultural Officers was selected by using simple random sampling. Emotional Intelligence was the dependent variable of the study. A well-structured interview schedule was used for collecting the data from the respondents. The data were tabulated and inferences were drawn after appropriate statistical analysis. The results showed that the scenario of existing status of emotional intelligence skills of respondents was good as most of them were in medium to high category.